The new evolutionary economics - Dopfer, Kurt; Potts, Jason 1972- (Cheltenham, UK Edward Elgar Publishing Limited, 2014)
This three volume set gathers together selected key articles in evolutionary economics, ordering these into the domains of micro analysis (concerned with agents), meso analysis (concerned with rule populations and trajectories) and macro analysis (concerned with the structure and development of the whole economy). This authoritative collection, with an original introduction by the editors, will be of interest to scholars and researchers seeking to understand how evolutionary economics fits together and to advance such an integrated approach.
Volume 3 -- Richard P.F. Holt, J. Barkley Rosser, Jr. and David Colander (2011), 'The Complexity Era in Economics', Review of Political Economy, 23 (3), July, 357-69 -- Peter M. Allen (2005), 'Understanding Social and Economic Systems as Evolutionary Complex Systems', in KurtDopfer (ed.), The Evolutionary Foundations of Economics, Chapter 13, Cambridge, UK and New York, NY: Cambridge University Press, 431-58 -- Sylvie Geisendorf (2009), 'The Economic Concept of Evolution: Self-Organization or Universal Darwinism?', Journal of Economic Methodology, 16(4), December, 377-91 -- John Foster (2011), 'EvolutionaryMacroeconomics: A Research Agenda', Journal of Evolutionary Economics, 21 (1), February, 5-28 -- DomenicoDelli Gatti, Edoardo Gaffeo and Mauro Gallegati (2010), 'Complex Agent-Based Macroeconomics: A Manifesto for a New Paradigm', Journal of Economic Interaction and Coordination, 5 (2), December, 111-35 -- Bart Verspagen (2002), 'Evolutionary Macroeconomics: A Synthesis between Neo-Schumpeterian and Post-Keynesian Line of Thought', Electronic Journal of Evolutionary Modeling and Economic Dynamics, article 1007: http//www.e-jemed.org/1007/index.php, i, 1-21 -- Giovanni Dosi, Giorgio Fagiolo and Andrea Roventini (2010), 'Schumpeter Meeting Keynes: A Policy-Friendly Model of Endogenous Growth and Business Cycles', Journal of Economic Dynamics and Control, 34 (9),September, 1748-67 Ping Chen (2005), 'Evolutionary Economic Dynamics: Persistent Cycles, Disruptive Technology and the Trade-Off between Stability and Complexity', in Kurt Dopfer (ed.), The Evolutionary Foundations of Economics, Chapter 15, Cambridge, UK and New York, NY: Cambridge University Press, 472-505 -- Fulvio Castellacci (2009), 'The Interactions between National Systems and Sectoral Patterns of Innovation: A Cross-Country Analysis of Pavitt's Taxonomy', Journal of Evolutionary Economics, 19 (3), June, 321-47 -- Pier Paolo Saviotti and Andreas Pyka (2008), 'Micro and Macro Dynamics: Industry LifeCycles, Inter-Sector Coordination and Aggregate Growth', Journal of Evolutionary Economics, 18 (2), April, 167-82 -- Michael Peneder (2003), 'Industrial Structure and Aggregate Growth', Structural Change and Economic Dynamics, 14 (4), December, 427-48 -- Richard R. Nelson (2008), 'Economic Development from the Perspective of Evolutionary Economic Theory', Oxford Development Studies, 36 (1), March, 9-21 -- J. Stanley Metcalfe (2001), 'Evolutionary Approaches to Population Thinking and the Problem of Growth and Development', in Kurt Dopfer (ed.), Evolutionary Economics: Program and Scope, Chapter 4, Boston, MA, Dordrecht, The Netherlands and London, UK: Kluwer Academic Publishers, 141-64 -- Gerald Silverberg and Bart Verspagen (2005), 'Evolutionary Theorizing on Economic Growth', in Kurt Dopfer (ed.), The Evolutionary Foundations of Economics, Chapter 16, Cambridge, UK and New York, NY: Cambridge University Press, 506-39 -- J. Stan Metcalfe, John Foster and Ronnie Ramlogan (2006), 'Adaptive Economic Growth', Cambridge Jounal of Economics, 30 (1), January, 7-32 -- Pier Paolo Saviotti and Andreas Pyka (2004), 'Economic Development, Qualitative Change and Employment Creation', Structural Change and Economic Dynamics, 15 (3), September,265-87 -- Bengt-Åke Lundvall (1988), 'Innovation as an Interactive Process: From User-Producer Interaction to theNational System of Innovation', in Giovanni Dosi, Christopher Freeman, Richard Nelson, Gerald Silverberg and Luc Soete (eds), Technical Change and Economic Theory, Chapter 17, London, UK and New York, NY: Pinter Publishers, 349-69 -- Chris Freeman (1995), 'The "National System of Innovation" in Historical Perspective', Cambridge Journal of Economics, 19 (1), February, 5-24 -- Tim Kastelle, Jason Potts and Mark Dodgson (2009), 'The Evolution of Innovation Systems', Paper presented at the DRUID Summer Conference, 2009, i, 1-24 -- Ulrich Witt (2003), 'Economic Policy Making in Evolutionary Perspective', Journal of Evolutionary Economics, 13 (2), April, 77-94 -- Uwe Cantner and Andreas Pyka(2001), 'Classifying Technology Policy from an Evolutionary Perspective', Research Policy,30 (5), May, 759-75 -- Bengt-Åke Lundvall and Susana Borrás (2005), 'Science, Technology, and Innovation Policy', in Jan Fagerberg, David C. Mowery and Richard R. Nelson (eds), The Oxford Handbook of Innovation, Chapter 22, Oxford, UK and New York, NY: Oxford University Press, 599-631 -- Uwe Cantner, Bernd Ebersberger, Horst Hanusch, Jens J. Krüger and Andreas Pyka (2004), 'The Twin Peaks inNational Income: Parametric and Nonparametric Estimates', Revue économique, 55 (6), November, 1127-44 -- Carlota Perez (1985), 'Microelectronics, Long Waves and World Structural Change: New Perspectives for Developing Countries', World Development, 13 (3), March, 441-63 -- Dan Johansson (2010), 'The Theory of the Experimentally Organized Economy and Competence Blocs: An Introduction', Journal of Evolutionary Economics, 20 (2), April, 185-201 -- Kurt Dopfer and Jason Potts (2008), 'Generic Policy', in The General Theory of Economic Evolution, Chapter 7, London, UK and New York, NY: Routledge, 167-78, references
Includes bibliographical references.
Keywords: Evolutionary economics